Research on barker coded excitation method for magneto-acoustic imaging. (January 2018) - Zhang, Shunqi; Zhou, Xiaoqing; Liu, Shikun; Yin, Tao; Liu, Zhipeng
Highlights: A method to improve SNR in Magneto-acoustic Imaging. This study developed a Barker coded excitation and pulse compression method. The SNR of magneto-acoustic signal is improved by 21.5 dB. The processing time of proposed method can be shortened by 95.8%. Abstract: Functional imaging method of biological electrical characteristics based on magneto-acoustic effect gives valuable information of tissue in early tumor diagnosis. Common exciting and measuring method is to use single pulse. The imaging quality and the imaging speed are limited by the signal to noise ratio (SNR). In this study, we propose a processing method based on coded excitation and pulse compression to improve SNR of magneto-acoustic imaging. Barker code is widely used in ultrasonic signal processing, which can effectively improve the signal to noise ratio. It is introduced to increase SNR of the magneto-acoustic signal. Simulations on magneto-acoustic signal and pulse compressed signal under Barker coded excitation with a group of bit lengths are computed. Experiments on sample made of pork and graphite slices are done to validate the proposed coded excitation method. The pork sample is imaged to validate this method. SNR is investigated using Barker codes with different bits. The results showed, the SNR of magneto-acoustic signal is improved by the coded excitation. When 13 bit Barker code mode is adopted as the exciting signal, SNR improved by 21.5 dB. For a similar SNR improvement, the processing time of coded excitation method can be shortened by 95.8% compare with single pulse excitation method. In a conclusion, the coded excitation method is effective to improve the magneto-acoustic signal SNR and imaging quality. It also improves the magneto-acoustic imaging speed.